Collaborative model of care between Orthopaedics and allied healthcare professionals trial (CONNACT) – a feasibility study in patients with knee osteoarthritis using a mixed method approach - Tan, Bryan Yijia (2021)
Background: Osteoarthritis is a leading cause of global disability resulting in significant morbidity and cost to the healthcare system. Current guidelines recommend lifestyle changes such exercises and weight loss as first line treatment prior to surgical consideration. Our current model of care is inefficient with suboptimal allied health intervention for effective behaviour changes. A 12-week community based, individualized, multidisciplinary new model of care for knee osteoarthritis was developed in light of current deficiencies. Methods: The primary aim of this study was to determine the feasibility of a full randomized controlled trial evaluating this new model of care using pre-defined progression criteria. The secondary aim was to optimize the intervention and study design through a process evaluation. A pilot exploratory, parallel arm, single blinded randomized trial design using a mixed method approach was utilized. Progression criteria for a full trial including key domains of patient recruitment and retention, outcome measure acceptability and improvement, adverse events were developed. The primary outcome measure was the Knee Injury and Osteoarthritis Outcome Score (KOOS) at baseline and 12-weeks. Secondary outcomes included quality of life, functional and psychological assessments. Semi-structured interviews were conducted with the patients at 12-weeks. Results: 20 patients (3 males, 17 females) were randomized (10 intervention, 10 control). Intervention arm patients reported better improvements in their knee function, quality of life, psychological outcome, dietary improvement and weight loss compared to the control arm at 12-weeks. Semi-structured interviews revealed several themes pertaining to feasibility and intervention optimization. 5 out of the 6 progression criteria’s domains were met (recruitment criteria not met). Conclusion: This pilot has demonstrated the feasibility of a full randomized control trial investigating the potential effectiveness of the new proposed model of care for knee osteoarthritis using pre-defined progression criteria and process evaluation. Results from the qualitative study were used to modify and improve the intervention content, delivery model and study design for a large effectiveness-implementation hybrid randomized control trial that is currently underway.